Paradiplomasi Pemerintah Kabupaten Pesisir Barat dalam Kerja Sama Penyelenggaraan World Surf League Krui Pro - Muhammad Rizki Fadillah; Moh Nizar; Luerdi Luerdi (Government Science Department , Faculty of Social and Political Science - University of Lampung. Journal of Government and Social Issues (JGSI), 2026)
The Pesisir Barat Regency in Lampung Province sought to leverage its local potential, namely its coastal waves, by partnering with the international actor, the World Surf League, to host the WSL Krui Pro. Such a phenomenon deserves investigation, as international cooperation – also known as paradiplomacy – is pursued by subnational actors, which commonly lack bargaining power on the global stage. Using a qualitative research method with descriptive analysis and the concept of paradiplomacy, this research sheds light on the model and purpose of such a local government’s paradiplomatic practice in organizing an international surfing event. Data was gathered through interviews and relevant documents. The findings show that paradiplomacy by the Pesisir Barat Regency took shape in the model of regional paradiplomacy, which was complementary and opportunity-oriented. In addition, the local government was pursuing economic, cultural, and technical interests that belong to the first and second layers of paradiplomacy. Represented by the case study of the Pesisir Barat Regency Government in this paper, the foreign relations or cooperation by Indonesian subnationals can occur in the bottom-up process, even by regions that are underdeveloped and not used to getting involved in foreign affairs.